2003
DOI: 10.1161/01.str.0000090471.28672.65
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Patients Have an Impaired Cerebral Vasodilatory Response to Hypercapnia Under Propofol Anesthesia

Abstract: Background and Purpose-The purpose of this study was to examine the effects of diabetes mellitus and its severity on the cerebral vasodilatory response to hypercapnia. Methods-Thirty diabetic patients consecutively scheduled for elective major surgery were studied. After induction of anesthesia, a 2.5-MHz pulsed transcranial Doppler probe was attached to the patient's head at the right temporal window, and mean blood flow velocity of the middle cerebral artery (Vmca) was measured continuously. After the baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 28 publications
3
78
1
Order By: Relevance
“…It has also been demonstrated that impairment in cerebrovascular reactivity correlates with duration of the disease and develops parallel with other vascular complications. 5,18 In the present study, we also demonstrated an increased baseline pulsatility indices and a reduced reactivity of the cerebral arterioles against both vasodilatory and vasoconstrictor stimuli in diabetic patients. A higher activity of vasoactive substances has been described in earlier experiments in DM, 19,20 which gives a good explanation for the increased arteriolar tone observed in diabetic patients at baseline measurements.…”
Section: Discussionsupporting
confidence: 76%
“…It has also been demonstrated that impairment in cerebrovascular reactivity correlates with duration of the disease and develops parallel with other vascular complications. 5,18 In the present study, we also demonstrated an increased baseline pulsatility indices and a reduced reactivity of the cerebral arterioles against both vasodilatory and vasoconstrictor stimuli in diabetic patients. A higher activity of vasoactive substances has been described in earlier experiments in DM, 19,20 which gives a good explanation for the increased arteriolar tone observed in diabetic patients at baseline measurements.…”
Section: Discussionsupporting
confidence: 76%
“…The regional differences in cerebral metabolic capacity may explain increased sensitivity to hyperglycemia in the cerebral cortex (28). Previous studies described reduced or normal CO 2 reactivity in diabetes (32,33). This study applying CASL for evaluation of CBF and CO 2 vasoreactivity demonstrated that CASL is a reliable tool for assessment of flow reserve in an elderly diabetic population.…”
Section: Regional Perfusion and Brain Volumes In Diabetesmentioning
confidence: 60%
“…A decreased CVR is indicative of preexisting vasodilation, which reflects reduced reserve capacity of cerebral autoregulation [19]. The cerebral vasodilatory capacity is impaired in patients with type 2 DM [51,52,53]. …”
Section: Discussionmentioning
confidence: 99%